Field Ion Microscopy of Tungsten Nano-Tips Coated with Thin Layer of Epoxy Resin - Sobola, Dinara; Alsoud, Ammar; Knápek, Alexandr; M. Hamasha, Safeia; Mousa, Marwan S. Mousa; Schubert, Richard; Neubauerová, Pavla; Škarvada, Pavel (MDPI, 2024)
This paper presents an analysis of the field ion emission mechanism of tungsten-epoxy nanocomposite emitters and compares their performance with that of tungsten nano-field emitters. The emission mechanism is described using the theory of induced conductive channels. Tungsten emitters with a radius of 70 nm were fabricated using electrochemical polishing and coated with a 20 nm epoxy resin layer. Characterization of the emitters, both before and after coating, was performed using electron microscopy and energy-dispersive X-ray spectroscopy (EDS). The Tungsten nanocomposite emitter was tested using a field ion microscope (FIM) in the voltage range of 0-15 kV. The FIM analyses revealed differences in the emission ion density distributions between the uncoated and coated emitters. The uncoated tungsten tips exhibited the expected crystalline surface atomic distribution in the FIM images, whereas the coated emitters displayed randomly distributed emission spots, indicating the formation of induced conductive channels within the resin layer. The atom probe results are consistent with the FIM findings, suggesting that the formation of conductive channels is more likely to occur in areas where the resin surface is irregular and exhibits protrusions. These findings highlight the distinct emission mechanisms of both emitter types.

This paper presents an analysis of the field ion emission mechanism of tungsten-epoxy nanocomposite emitters and compares their performance with that of tungsten nano-field emitters. The emission mechanism is described using the theory of induced conductive channels. Tungsten emitters with a radius of 70 nm were fabricated using electrochemical polishing and coated with a 20 nm epoxy resin layer. Characterization of the emitters, both before and after coating, was performed using electron microscopy and energy-dispersive X-ray spectroscopy (EDS). The Tungsten nanocomposite emitter was tested using a field ion microscope (FIM) in the voltage range of 0-15 kV. The FIM analyses revealed differences in the emission ion density distributions between the uncoated and coated emitters. The uncoated tungsten tips exhibited the expected crystalline surface atomic distribution in the FIM images, whereas the coated emitters displayed randomly distributed emission spots, indicating the formation of induced conductive channels within the resin layer. The atom probe results are consistent with the FIM findings, suggesting that the formation of conductive channels is more likely to occur in areas where the resin surface is irregular and exhibits protrusions. These findings highlight the distinct emission mechanisms of both emitter types.
Field Ion Microscopy of Tungsten Nano-Tips Coated with Thin Layer of Epoxy Resin
Keywords: field ion emission; tungsten atomic distribution; epoxy molecular distribution; composite field emitter; composite electron sources; field ion emission; tungsten atomic distribution; epoxy molecular distribution; composite field emitter; composite electron sources